Diseases of glycosylation beyond classical congenital disorders of glycosylation - Hennet, Thierry (Biochimica et biophysica acta, 2012)
Diseases of glycosylation are rare inherited disorders, which are often referred to as congenital disorders of glycosylation (CDG). Several types of CDG have been described in the last decades, encompassing defects of nucleotide-sugar biosynthesis, nucleotide-sugar transporters, glycosyltransferases and vesicular transport. Although clinically heterogeneous, most types of CDG are associated with neurological impairments ranging from severe psychomotor retardation to moderate intellectual disabilities. CDG are mainly caused by defects of N-glycosylation, owing to the simple detection of under-glycosylated serum transferrin by isoelectric focusing. In the last years, several disorders of O-glycosylation, glycolipid and glycosaminoglycan biosynthesis have been described, which are known by trivial names not directly associated with the family of CDG. The present review outlines 64 gene defects affecting glycan biosynthesis and modifications, thereby underlining the complexity of glycosylation pathways and pointing to unexpected phenotypes and functional redundancies in the control of glycoconjugate biosynthesis. The increasing application of whole-genome sequencing techniques unravels new defects of glycosylation, which are associated to moderate forms of mental disabilities. The knowledge gathered through the investigation of CDG increases the understanding of the functions associated to protein glycosylation in humans. This article is part of a Special Issue entitled Glycoproteomics. ► Diseases of glycosylation are classified as congenital disorders of glycosylation. ► CDG are rare inherited diseases with a broad range of clinical manifestation. ► To date 64 gene defects have been identified as cause of CDG. ► Genotype–phenotype comparisons reveal unexpected functional redundancies.